Effect of Humic Acid Fertilizer on Mercury Release from Greenhouse Soils - Z. Zhao, L. Y. Long, H. Gu and R. G. Sun (Nature Environment and Pollution Technology, 2024)
The elemental mercury (Hg0) release characteristics from the Hg-contaminated soil applied with Humic acid fertilizer (HAF) in the greenhouse were identified. The adsorption features of mercuric ion (Hg2+) on HAF under different reaction times and pH were investigated to elucidate the influencing mechanism of HAF on soil Hg0 release. Besides, the microstructure of HAF loading with Hg2+ was characterized by using Fourier transform infrared spectroscopy (FTIR) and scanning electron micrograph-energy dispersive spectrometry–EDS). The results showed that with the increasing HAF dosage, soil oxidation-reduction potential (Eh), and organic matter (SOM) content, as well as the decreasing soil pH, the soil Hg0 release fluxes showed a decreasing tendency. The soil pH, Eh, SOM, and total Hg content are the key factors that can affect the soil Hg0 release fluxes. The interior air temperature, light intensity, soil moisture, and soil temperature have little impact on soil Hg0 release fluxes when the greenhouse soil is applied with HAF. The HAF can immobilize Hg2+ and reduce its activity by surface precipitation and specific adsorption, then affecting the soil Hg0 release fluxes. The results of this study provide a basis for the application of HAF to reduce soil Hg0 release fluxes in the greenhouse of Hg-contaminated areas.